Hydraulic Characteristics of Penang’s Main River - Anthony Lee, Adelbert; Tan, Lai Wai (Recent Trends in Civil Engineering and Built Environment, 2024)
The water supply in Penang has been severely depleted. Due to a lack of drinking water, Penang inhabitants are experiencing a shortage of both human and animal populations. Humans need water to survive. Governments at all levels must find a solution. Higher-ups will likely be asked to hire workers for dams, reservoir, and water treatment facilities. Examine the river before you start construction. When it comes to providing water to homes and businesses, the river's flow is critical. Therefore, determining the river's hydraulic qualities is essential. To validate or determine the flow rate of Penang's key rivers, this study is critical. Higher river flow rates, as we all know, equate to greater efficiency and, as a result, lower costs. Using this method, the large flow coordinates can be found. In order to verify the river's length, we'll collect data with AutoCAD. In order to get more accurate results, Google Earth is needed to pinpoint the river's position. Last but not least, we'll use Manning's Equation to calculate flowrate. At 229.4 metre per second, Sungai Ara is Penang's river system's highest peak flow. This is the finest river to construct a dam, reservoirs, or treatment plant on.